Placenta Percreta at 17 Weeks with Consecutive Hysterectomy: A Case Report and Review of the Literature - Natasha Gupta; Anu Gupta; Marlene Green; Hyung Shik Kang; Josef Blankstein (Case Reports in Obstetrics and Gynecology)
Placenta percreta in early pregnancy is an extremely rare but life-threatening complication, for which very few cases have been reported in the literature worldwide, none from the United States. We report a patient with two previous cesarean deliveries, who presented with incomplete abortion at 17 weeks and underwent dilatation and curettage. She was found to have retained, adherent placenta that led to extensive hemorrhage, requiring emergency supracervical hysterectomy. Postoperative course was also complicated by severe consumption coagulopathy, necessitating reexploration after hysterectomy. Pathology revealed a placenta percreta. Patient lost more than 8000 cc blood through the 2 surgeries, received massive transfusions due to severe disseminated intravascular coagulopathy (DIC), and underwent a complicated surgery because of great difficulty in separating lower uterine segment and cervix from the bladder. Abnormal placentation in early pregnancy has increased in prevalence due to marked rise in cesarean deliveries and curettages in recent decades. We reviewed all reported cases of first and second trimester placenta percreta in the literature, to emphasize the early recognition of abnormal placentations in patients with risk factors, consider prenatal evaluation in such patients, anticipate complicated placental implantations during termination procedures, and prevent associated maternal morbidity and mortality.